Happy Valentine's day, Mouse! - Numeroff, Laura Joffe; Bond, Felicia (New York : Balzer + Bray, 2009)
"Join Mouse from 'If you give a mouse a cookie' as he celebrates Valentine's Day with all the friends he loves" -- p. [4] of cover.
"An If you give-- book" -- p. [1] of cover.
On board pages.
Keywords: Mice -- Juvenile fiction; Valentines -- Juvenile fiction; Friendship -- Juvenile fiction; Valentine's Day -- Juvenile fiction; Board books; Mice -- Fiction; Valentines -- Fiction; Friendship -- Fiction; Valentine's Day -- Fiction